2013
DOI: 10.1155/2013/635384
|View full text |Cite
|
Sign up to set email alerts
|

Design, Synthesis, and In Vitro Antimicrobial Evaluation of Fused Pyrano[3,2-e]tetrazolo[1,5-c]pyrimidines and Diazepines

Abstract: A series of novel pyranochromene-containing tetrazoles fused with pyrimidinethiones, pyrimidines, and diazepines 3a–f, 4a–f, and 5a–f were synthesized by condensation of the corresponding tetrazoles 2a–f with carbon disulfide, benzaldehyde, and 4-methoxy phenacyl bromide, respectively. The compound 2a–f was obtained by reaction of pyrano[3,2-c]chromenes 1a–f with sodium azide. The structures of the newly synthesized compounds 2a–f to 5a–f were established on the basis of their elemental analyses, IR, 1H NMR, 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 28 publications
(23 reference statements)
0
2
0
Order By: Relevance
“…Fluconazole was used as a reference antifungal agent. The study showed that compounds 34 , 35 , 36 and 37 showed significant antibacterial and antifungal activities compared with other tested samples [ 45 ].…”
Section: Biological Activity Of Tetrazolium Derivativesmentioning
confidence: 99%
“…Fluconazole was used as a reference antifungal agent. The study showed that compounds 34 , 35 , 36 and 37 showed significant antibacterial and antifungal activities compared with other tested samples [ 45 ].…”
Section: Biological Activity Of Tetrazolium Derivativesmentioning
confidence: 99%
“…Dihydropyrano [c]chromenes and their analogs are important compounds because they have diversity in several biological features 3 , which are antihypertensive, anticoagulation 4 , anti-cancer 5 , and anti-anaphylactic action 6 .…”
Section: Introductionmentioning
confidence: 99%
“…The development of tetrazole chemistry has been largely associated with the widespread use of these compounds in medicine, biochemistry, agriculture, material sciences, etc. [11][12][13][14][15][16]. Also, tetrazole possesses a unique combination of properties of substantial thermal stability along with high positive enthalpy rates of formation and the highest nitrogen content among organic compounds with relatively high stability [17].…”
Section: Introductionmentioning
confidence: 99%